Protein Fibrillar Hydrogels for three-Dimensional Tissue Engineering. (31st August 2009) - Yan, Hui; Nykanen, Antti; Ruokolainen, Janne; Farrar, David; Miller, Aline F.
Abstract : Protein self-assembly into highly ordered fibrillar aggregates has attracted increasing attention over recent years, due primarily to its association with disease states such as Alzheimer's. More recently, however, research has focused on understanding the generic behavior of protein self-assembly where fibrillation is typically induced under harsh conditions of low pH and/or high temperature. Moreover the inherent properties of these fibrils, including their nanoscale dimension, environmental responsiveness, and biological compatibility, are attracting substantial interest for exploiting these fibrils for the creation of new materials. Here we will show how protein fibrils can be formed under physiological conditions and their subsequent gelation driven using the ionic strength of cell culture media while simultaneously incorporating cells homogeneously throughout the gel network. The fibrillar and elastic nature of the gel have been confirmed using cryo-transmission electron microscopy and oscillatory rheology, respectively; while cell culture work shows that our hydrogels promote cell spreading, attachment, and proliferation in three dimensions.